Effect of volatile boron species on the microstructure and composition of (La,Sr)MnO3 and (La,Sr)(Co,Fe)O3 cathode materials of solid oxide fuel cells - Chen, Kongfa; Hyodo, J.; Zhao, L.; Ai, Na; Ishihara, T.; Jiang, San Ping (The Electrochemical Society, Inc, 2013)
Effect of volatile boron species on the microstructure and composition of dense La0.8Sr0.2MnO3 (LSM) and La0.6Sr0.4Co0.2Fe0.8O3 (LSCF) bar samples is studied in detail using secondary ion mass spectroscopy (SIMS) technique. Prior to the characterization, the bar samples were heat-treated at 800°C in air in the presence of borosilicate glass for 7 and 30 days. SIMS detected the deposition of boron as well as sodium and potassium on the surface and in the bulk of the bar samples. The boron deposition results in significant microstructure and composition changes. SIMS, EDS and XRD confirm that Sr in the form of SrB2O4 is enriched on the outmost surface, leading to the Sr-deficient in the adjacent layer in the bulk. In the case of LSM bar samples, the interaction between boron and LSM leads to the formation of LaBO3 and consequently the decomposition of the LSM perovskite structure. The present study demonstrates the remarkable detrimental effect of volatile boron species on the microstructure of the LSM and LSCF cathode materials of solid oxide fuel cells, and LSCF is more reactive with boron as compared to LSM.